A Peranan Kepemimpinan Kepala Sekolah Dalam Meningkatkan Manajemen Pendidikan - Imam Turmudi (Al-Riwayah : Jurnal Kependidikan, 2021)
This research is motivated by the role of principal leadership in improving education management. The success and failure of an organization in achieving the goals that have been set depends very much on the role and ways of leading practiced by the leader, in the context of the educational institution is the principal. Recognized or not, the principal is one of the important elements of educational activities. Improving the quality of education in schools and as the highest authority in schools is a professional and moral responsibility to make the school the center of science, culture, and the development of the nation's personality. Given his considerable responsibility, school principals are required to have more and adequate abilities. One of the duties of the principal is as a manager, which is required to be able to complete administrative and supervisory tasks. This study used a descriptive qualitative approach with the research location at Tawakkal Junior High School (SMP) Denpasar. Data collection techniques using observation, interviews and documentation. Meanwhile, data analysis was carried out systematically starting from data reduction, data presentation, drawing conclusions and verification of results. From the results of the research, the authors concluded that the principal as the leader of educational institutions has been able to become a driving force for school management in a more advanced direction, upholds quality and morality and has been able to implement various management functions in managing educational organizations / institutions based on the principles -management principles and Islamic religious values. This can be proven from the academic achievements that have been obtained in value which has continued to increase, especially in the last three academic years. Likewise, the non-academic achievements he has achieved so far are quite encouraging